Mendidik Siswa dengan Prinsip Keteladanan - Muhammad Akbar (Jurnal Teknologi Pendidikan Madrasah, 2019)
The teacher's job is not only limited to doing a science transformation, but also must set a good example. Exemplary in education is part of a number of the most effective and effective methods in preparing and forming children morally, spiritually, and socially. Therefore, teachers should be able to be good role models for their students. Related to this, there are several things that must be done by the teacher, including: (1) Always showing a good attitude in front of students, (2) Never having been selfish or willing to win themselves in any case, (3) always doing good to others without expecting reward. (4) Always treat students well as they want to be treated by others well too.